Preservation and stability of cell therapy products: recommendations from an expert workshop. (July 2017) - Stacey, Glyn N; Connon, Che J; Coopman, Karen; Dickson, Alan J; Fuller, Barry; Hunt, Charles J; Kemp, Paul; Kerby, Julie; Man, Jennifer; Matejtschuk, Paul; Moore, Harry; Morris, John; et al.
If the field of regenerative medicine is to deliver therapies, rapid expansion and delivery over considerable distances to large numbers of patients is needed. This will demand efficient stabilization and shipment of cell products. However, cryopreservation science is poorly understood by life-scientists in general and in recent decades only limited progress has been made in the technology of preservation and storage of cells. Rapid translation of new developments to a broader range of cell types will be vital, as will assuring a deeper knowledge of the fundamental cell biology relating to successful preservation and recovery of cell cultures. This report presents expert consensus on these and other issues which need to be addressed for more efficient delivery of cell therapies.